DAMPAK NILAI IMPOR DAN EKSPOR INDONESIA TERHADAP PENANAMAN MODAL ASING AS DI INDONESIA 2000-2020 - Widya, I Gusti Ngurah Made Parama; Sugianto, Sugianto (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.07.TAHUN.2022DO - 10.24843/EEB.2022.v11.i07.p11, 2022)
This study aims to understand Indonesia's exports -the value of US imports to Indonesia from 2000 to 2020. The independent variables of this study are Indonesia's export value from 2000 to 2020 (X1), Indonesia's import value from 2000 to 2020 (X2) and the dependent variable i.e. Indonesia's foreign countries in the United States from 2000 to 2020. It is a direct investment (Y). The data used is from the official website of the Indonesian Central Bureau of Statistics. The data analysis used is a multiple regression analysis. The stimulus test (F-test) results show that the simultaneous value of Indonesia's imports and exports does not have a significant impact on US foreign investment in Indonesia. On the other hand, the partial test (t-test) results show that the import and export variables do not show a partially significant effect on US foreign investment in Indonesia from 2000 to 2020